IMPLEMENTATION OF LEAN SIX SIGMA IN HOSPITAL ENVIRONMENTS: A COMPARATIVE ANALYSIS OF FINANCIAL AND OPERATIONAL RESULTS - Garcia Medeiro, Juliana (Revista Gênero e Interdisciplinaridade, 2025)
This article presents a systematic literature review on the implementation of the Lean Six Sigma (LSS) methodology in hospital environments, with the objective of comparatively analyzing financial and operational results. The healthcare sector faces growing challenges related to costs, efficiency, and quality of care, making the adoption of continuous improvement strategies imperative. The methodology of this study involved a structured search in international databases (PubMed/PMC, Emerald Insight, Scopus, Web of Science, and Google Scholar), followed by the analysis and synthesis of case studies, review articles, and empirical research using rigorous inclusion and exclusion criteria. The results indicate that the implementation of LSS generates consistent benefits, including improvements in operational indicators such as reduction in waiting time (up to 50% in some cases), optimization of patient flow, and increased safety. Financially, although there are reports of significant cost reductions (average of 1,500,000 per project) and positive Return on Investment (ROI) (2.5–4x), measurement is complex due to the difficulty of monetizing intangible benefits. The analysis revealed that factors such as leadership commitment, integration of LSS into the organizational culture, and adequate training are crucial for success. It is concluded that LSS is a valuable strategic approach for hospital management, but that the literature still lacks longitudinal studies, comparisons with control groups, and standardized value measurement frameworks for the sector. It is suggested that future research focus on these gaps to strengthen the evidence base and guide managerial practice.